Communication – the essential skill in contemporary nursing - Kekus, Divna; Stanisavljevic, Sanja; Lazarevic, Andjelka; Dragumilo, Aleksandra (Nursing in the 21st Century, 2012)
COMMUNICATION – THE ESSENTIAL SKILL IN CONTEMPORARY NURSINGIntroduction. By nature, communication in health care is transdisciplinary and draws on many areas, with the complexity of achieving behavioral and social changes. WHO has identified the quality of communication as one of the five skills necessary for a healthy and happy life.Aim. Highlight the importance of health care communication as an integrative factor of modern nursing in clinical practice.Material and methods. Descriptive analytical approach.Results: The work concisely represents the essence of health care communication as the interaction and exchange of information between all participants in the health system (patients, their families, medical staff, associates, media, government officials ...). It is spoken about it as a specific form of social communication that takes place on the subtle emotional and intellectual level, where it is important to appreciate the character of all participants included. The concept of communication competence is established and all the specific skills necessary for successful communication are determined. Three basic levels of therapeutic communication and interaction are presented. The use of the concept of transmission of communication in the modern approach to this phenomenon is explained.Conclusions. Interpersonal communication in health care in addition to the usual message transmission partly has characteristics of official communication, because it also means a professional activity. Increasing awareness of the importance of communication allows the choice of the communication methods, the value framework and the communication skills and characters used in communication. Understanding the rules and structures of communication helps in the formation of a viable and cost effective professional communication in the field of nursing activities. Developed skills of effective communication can be understood as a form of quality assurance in nursing.